The Sublime and the Other - White, Richard John (Heythrop journal, 1997)
What is the philosophical significance of the “sublime”, and does this concept still have any relevance to contemporary life? In this essay, I argue that the experience of the sublime is exceptionally important, insofar as it presents us with a general model for the experience of otherness, the encounter with transcendence itself, which might reasonably be viewed as impossible. As Rudolf Otto suggested, the experience of the sublime is closely related to the experience of the sacred; and even in Burke and Kant, the sublime is to be grasped as both an aesthetic and a religious experience which finally opens the individual to that which is greater than herself. Thus, the sublime has become a major theme in postmodern theory, precisely because it gives us access to the sacred and that which is wholly “other.”